Pengaruh Perceived Value dan Promotion terhadap Revisit Intention dengan Kepuasan sebagai Intervening - Rina Anggraeni; Mohamad Rizan; Basrah Saidani (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
This study aims to determine the effect of perceived value and promotion on revisit intention with satisfaction as an intervention. Data was obtained by using a survey method with purposive sampling on a liktert scale to 220 respondents on visitors of Dunia Fantasi. The data analysis method used in this research is Structural Equation Modeling (SEM) using LISREL software version 8.8. The results show that there is a significant positive effect of perceived value on satisfaction, there is a significant positive effect of promotion on satisfaction, there is a significant positive effect of perceived value on revisit intention, there is a significant positive effect of promotion on revisit intention, there is a significant positive effect of satisfaction on revisit intention, there is a significant positive effect of satisfaction on revisit intention. There is a significant effect of perceived value on revisit intention through satisfaction, and there is a significant effect of promotion on revisit intention through satisfaction. Penelitian ini bertujuan untuk mengetahui pengaruh perceived value dan promotion terhadap revisit intention dengan satisfaction sebagai intervening. Data diperoleh dengan menggunakan metode survei dengan purposive sampling secara skala liktert kepada 220 responden pengujung Dunia Fantasi. Metode analisis data yang digunakan dalam penelitian ini adalah Structural Equation Modeling (SEM) menggunakan Software LISREL versi 8.8. Hasil penelitian menunjukkan bahwa ada pengaruh positif signifikan perceived value terhadap satisfaction, terdapat pengaruh positif signifikan promotion terhadap satisfaction, terdapat pengaruh positif signifikan perceived value terhadap revisit intention, terdapat pengaruh positif signifikan promotion terhadap revisit intention, terdapat pengaruh positif signifikan satisfaction terhadap revisit intention, terdapat pengaruh signifikan perceived value terhadap revisit intention melalui satisfaction, dan terdapat pengaruh signifikan promotion terhadap revisit intention melalui satisfaction.